EFEKTIFITAS CONTENT DELIVERY NETWORK BERBASIS OPEN SOURCE DALAM SISTEM E-LEARNING - Nyoman Mirah Wedasari, Ni Luh; Aurelius Nurtanto Diaz, Ricky (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2017)
One of the new techniques in the process of sending data across a network is a Content Delivery Network. The main concept is to keep the copy of the CDN data from the main server, so that when the client accesses the specific content, data requested and received not from the main server, but rather from the server so that the process is more rapid CDN. With Indonesian internet condition that is not evenly distributed across its territory, the application of CDN is certainly can provide a significant impact for an electronic learning . With the concept of a CDN on e-learning, users can access data faster, so E-Learning content developers can more freely develop learning content in various formats, either text, images or audio/video. The process of data analysis in this study includes data analysis texts, pictures and videos, which will be measured is the speed of retrieve data as well as network traffic compared to client server communication process conventionally. The results of this research is Content Delivery Network more efisien than general network where the difference of load time between 0,5 ms to 1 ms.                                              Keywords : Content Delivery Network, E-Learning, Open Source